Financing of NCD Prevention in LMICs: Kenya Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad; Anum Siddiqui (Journal of the Pakistan Medical Association, 2026)
Objective: The objective of this study is to estimate spending on NCD prevention in Kenya and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Kenya spent an estimated 2.31 billion KSh on NCD prevention in 2015-16, constituting around 1.7% of total government health spending for the year. It is among the first African countries in the WHO African region to begin re-orienting its health system to address NCDs. Enablers include regional cooperation, local and global civil society advocacy, building integrated NCD programmes, progress in alcohol and tobacco taxation and regulation and institutions for inter-sectoral coordination. Challenges include devolution and subnational capacity gaps, perception of low political salience and visibility of NCD prevention interventions, poverty-related non-behavioural risk factors and regulatory gaps in nutrition policy. Opportunities identified including earmarking of revenues, county-level investment in health promotion, food systems approach to nutrition, ensuring timely disbursement to facilities, and interagency mechanisms between national and county governments. Conclusion: Kenya has made considerable progress in reorienting its health system towards NCD prevention and has also increased financing for NCD prevention in recent years, but it still remains less than 2% of government health spending. Increased population-level NCD prevention spending can help address the growing NCD burden and produce economic benefits. Keywords: Noncommunicable Diseases, Tobacco, Behaviour, Employees, Incidence, World Health Organization, Risk Factors, Diet, Nutrition Policy, Tobacco, Perception, Taxes, Poverty